American Foreign Policy Through The Lens of Rawls's Theory of Justice: Revisiting the Liberal Attitude Towards the Israeli-Palestinian Issue Post Oslo - Melouki Slimane; Zebda Noureddine (UNIVERSITÉ MOHAMED BOUDIAF - M’SILA, 2024)
The subject of social justice was and still is a demand and obsession of human societies and the aspiration and dream of many philosophers and political theorists, who presented a comprehensive vision on this subject through his books on politics, in which he directed his harsh criticism of the utilitarian trend that only concerned By focusing on the public good without concern for the rights of minorities. Rawls ‘s principles of justice as assume an original situation in which complete equality prevails within the group that will agree on those principles. Complete equality in an original situation means a situation in which class divisions, exploitation or class privileges do not exist. The strength and persistence of civic activities, throughout the history of the United States, in pursuit of justice. However, our influence and moral authority to move forward in spreading and strengthening democracy around the world have weakened as a result especially towards the Palestinian people exerted by the American foreign policy. The United States became the first country to recognize Israel on May 14, 1948, when President Harry Truman issued a statement of recognition following Israel's declaration of independence. The United States participates with Israel in high-level mutual operations, including military exercises, and weapons development.
Keywords: Justice; The United States; Dialogue; Peace Process; Foreign Policy; Israeli- Palestinian Issue